Evaluation of fiber optic installation methods, a case study on micro-trenching in Alberta, Canada - Hediyeh Vaseli; Leila Hashemian; Alireza Bayat; Leon Gay; Ian Williams; Jordan Melzer (Canadian Science Publishing, 2017)
Micro-trenching is an innovative and discreet utility installation method that includes the creation of a narrow trench to lay cable or conduit in the ground. To investigate the functionality and durability of micro-trenching in cold regions, two micro-trenching technologies were employed and monitored over the course of two winters in a parking lot in Edmonton, Alberta, Canada. During construction, productivity rate and generated waste material were studied. The installation's physical integrity and optical performance were also evaluated during the monitoring period. Physical integrity was assessed by monitoring the conduit location using ground-penetrating radar (GPR), and an optical time-domain reflectometer (OTDR) test was conducted to determine attenuation in performance. Results indicated that the installation experienced undesirable upward and downward movements in sections with high traffic load, which may be prevented with a more effective reinstatement method. However, the fiber's optical performance was not affected.